Taxonomy and molecular systematic position of freshwater genus Racekiela (Porifera: Spongillida) with the description of a new species from North-west Mexico. Issue 2 (17th February 2018) - Carballo, José L.; Cruz-Barraza, José A.; Yáñez, Benjamín; Gómez, Patricia
Abstract : Racekiela montemflumina sp. nov. is the first species of the genus Racekiela found in freshwater habitats from Mexico. The species is abundant in small creeks at the northern side of State of Durango, located between 2500 and 2700 m altitude. The new species description is provided together with in situ photographs of specimens, and SEM photographs of the spicules and gemmular structure. Two distinct classes of gemmuloscleres differing in size and shape (birotules and pseudobirotules) are present. The rotule of the birotula is discoidal, flat or slightly umbonate, with serrated margins and small crenulate teeth, or spines. The proportion of the diameter of the rotule vs. length of the shaft is the lowest of all the Racekiela species. Rotule of pseudobirotule is small, umbonate or with a prominent spike, and with hooks curved toward the shaft or almost straight. The birotules are embedded in the theca, but pseudobirotules protrude from the outer gemmular membrane. Fragments of cytochrome oxidase subunit I (COI) mtDNA, and internal transcribed spacers 1 and 2 (ITS1-5.8S-ITS2) rDNA were sequenced in order to establish the molecular identity and systematic position of genus Racekiela and the new species. COI showed an identical nucleotide composition with at least 11 spongillid-specimens from six previously sequenced species (GenBank). Phylogenetic analysis using the ribosomal region was concordant with previous information, which showed the monophyly of family Lubomirskiidae, and the non-monophyly of the families Spongillidae and Malawispongiidae. Specifically, Racekiela montemflumina sp. nov. erected as a sister clade of several species from the genera Ephydatia and Cortispongilla. Our species constitutes the first representative of genus Racekiela sequenced. This is also the first record of a freshwater sponge in Mexico in decades. www.zoobank.org/urn:lsid:zoobank.org:pub:71E826B6-59DC-475B-9391-27A7DED66E7A